2013
DOI: 10.1017/s0007114513002420
|View full text |Cite
|
Sign up to set email alerts
|

Low serum enterolactone concentration is associated with low colonicLactobacillusEnterococcuscounts in men but is not affected by a synbiotic mixture in a randomised, placebo-controlled, double-blind, cross-over intervention study

Abstract: Low serum enterolactone concentration is associated with low colonic Lactobacillus-Enterococcus counts in men but is not affected by a synbiotic mixture in a randomised, placebo-controlled, double-blind, cross-over intervention study AbstractThe aims of the present study were to assess the possible differences in faecal microbiota between men with a low serum enterolactone concentration and those with a high concentration, and to investigate the impact of a synbiotic mixture on serum enterolactone concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(46 reference statements)
1
13
1
Order By: Relevance
“…Divergent evidence is available on the anti-inflammatory properties of synbiotics and probiotics. In agreement with our study, consumption of the synbiotic containing 2 Lactobacillus strains, 1 Bifidobacterium strain, 1 Propionibacterium strain, and galacto-oligosaccharides (32 g/l) did not influence serum CRP levels among men with a low serum enterolactone concentration after cross-over at 6 weeks [35]. Furthermore, consumption of 1,500-mg probiotic capsules containing L. acidophilus, L. bulgaricus, L. bifidum, and L. casei twice daily did not show any significant changes in serum hs-CRP levels among diabetic patients after 6 weeks compared to the placebo [24].…”
Section: Discussionsupporting
confidence: 89%
“…Divergent evidence is available on the anti-inflammatory properties of synbiotics and probiotics. In agreement with our study, consumption of the synbiotic containing 2 Lactobacillus strains, 1 Bifidobacterium strain, 1 Propionibacterium strain, and galacto-oligosaccharides (32 g/l) did not influence serum CRP levels among men with a low serum enterolactone concentration after cross-over at 6 weeks [35]. Furthermore, consumption of 1,500-mg probiotic capsules containing L. acidophilus, L. bulgaricus, L. bifidum, and L. casei twice daily did not show any significant changes in serum hs-CRP levels among diabetic patients after 6 weeks compared to the placebo [24].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated potentially important roles for multiple bacterial species, including Peptostretococcus productus, Eggerthella lenta, Eubacterium, Butyribacterium methyltrophicum, Clostridium scindens, and Lactonifactor longovifromis (2630). A recent epidemiologic study observed that subjects with lower enterolactone concentration in serum also had lower fecal bacteria counts, especially for bacteria in the Lactobacillus-Enterococcus group (31). The target of low-dose triclosan is enoyl-acyl carrier protein reductase, which is essential for lipid biosynthesis in many, but not all, bacterial species (2).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is sound to hypothesize that gut microbial profiles influence enterolignan production phenotypes with possible ensuing consequences on physiological effects. Besides numerous in vitro work based on fermentation experiments using human fecal slurries , there are only two studies that investigated serum enterolactone concentrations and fecal bacteria in human subjects . The study by Holma et al .…”
Section: Introductionmentioning
confidence: 99%
“…The study by Holma et al . focused solely on the comparison between two groups of individuals (low or high serum enterolactone), fecal bacteria were analyzed in a targeted manner, and the intervention included a synbiotic mixture but no lignan substrates . Very recently, Hullar et al .…”
Section: Introductionmentioning
confidence: 99%